A general biochemical kinetics data fitting algorithm for quasi-steady-state detection - Daugmaudis, Justinas V.; Laurynėnas, Audrius; Kulys, Juozas; Ivanauskas, Feliksas (Lietuvos matematikos rinkinys, 2016)
We develop a general algorithm for fitting the biochemical kinetics data. The developed algorithm searches and analyzes numerous minima. This approach allows us to analyze biochemical data without a priori quasi-steady-state assumptions. The algorithm allows us to treat the biochemical kinetics data that has varying degree of steadiness. We test the approach by analyzing experiment data from 4-nitrophenyl phosphate hydrolysis with alkaline phosphatase.